The Romanian Jewry: Historical Destiny, Tolerance, Integration, Marginalisation - Gyémánt, Ladislau (Journal for the study of religions and ideologies, 2002)
To discuss what was the attitude of the Romanian society towards the increasing economic, social and political role of the Jews throughout history is one of the aims of this paper. Serban Papacostea, the outstanding specialist in mediaeval history, makes use of the syntagm hostile tolerance, which specified the general attitude towards the Jews of the Orthodox mediaeval world of Byzantine origin. Tolerance - defined the unlimited opportunity for Jews to be accepted, settle, move and act freely within the Romanian principalities, all the way to the status of possessing properties in Moldavia and Wallachia. There were, however, mixed feelings of hostility manifest at three distinct levels: mental, juridical and political. As for the mentalities, both popular and high brow education as well as prejudices held the Jews guilty for the death of Christ. Even if physically the Jewish presence in Romania has become symbolical, the history of the Jews, the traditions of the Jewish culture and spirituality, the imprint of the Jewish contribution on the emergence and development of the Romanian society will remain the perennial values of a historiography aspiring to fulfill its duty, forever preserved in the conscience of generations to come.